Perception of the Sports Social Environment After the Development and Implementation of an Identification Tool for Contagious Risk Situations in Sports During the COVID-19 Pandemic - Lete-Lasa, José Ramón; Martin-Acero, Rafael; Rico-Diaz, Javier; Gomez-Varela, Joaquín; Rio-Rodriguez, Dan (Frontiers in Psychology, 2021)
The present work details the methodological process for creating a tool for the identification of COVID-19 potential contagion situations in sport and physical education before, during, and after practice and competition. It is a tool that implies an educational and methodological process with all the agents of the sports system. This tool identifies the large number of interactions occurring through sports action and everything that surrounds it in training, competition, and its organization. The aim is to prepare contingency protocols based on an exhaustive analysis, risk detection, and proposal of contingency measures trying to reduce the residual risk to a minimum. In the second part, the results of the implementation of this tool in the sports system of Galicia (Spain) are shown revealing the change in perception about the coronavirus transmission in sport of the technicians and the problem for returning to sport for athletes under 18 years.